Modern Trends to Devote the Right to a Quality Environment - Issa, Bin Salih Muhammad Haj; Maria, Amrawi; A'amal, Bouhouia (Journal of Legal and Political Studies, 2020)
The issues related to the environmental protection constituted one of the most important emerging issues that modern legislation tried to respond to them for their connection with the basic areas of human life. For that reason, most countries have moved towards a gradual integration of the environmental dimension, starting with the enactment of relevant legal texts in its various fields, leading to its inclusion in the constitution, in different perceptions and formulations from one state to another. The constant of our study is, the dependence of countries in their study of the environmental dimension on a set of methods which are varied in their contents, but compatible in the essence of the issue related to the need to integrate the environmental dimension in the constitution; whether in the form of a right enjoyed by a particular group or an obligation imposed on the state or other public or private law people. Despite the constitutionality of the environmental dimension in most of the constitutions in the form of a right or an obligation, the sponsored texts raise many problems that legislative bodies must correct them, so that the text can perform the roles assigned to it.
Keywords: environmental protection; legal texts; environmental dimension; gradual integration